Zaedyus pichiy (Cingulata: Dasypodidae) - Superina, Mariella (2014)
Zaedyus pichiy (Desmarest, 1804) is a small armadillo commonly known as pichi. Like all armadillos, it bears a carapace of ossified dermal scutes covered by epidermal scales, but it is the only species that bears marginal scutes with sharply pointed apices. This diurnal, semifossorial species inhabits xeric shrublands and grasslands on sandy soils from central Argentina and Chile south to the Straits of Magellan. Z. pichiy has opportunistic omnivorous food habits and is the only xenarthran known to enter hibernation. It is listed as Near Threatened by the International Union for Conservation of Nature and Natural Resources; it is mainly threatened by humans who hunt it for food or sport.